CFD-model to predict the local and time-dependent scale formation of steels in air- and oxygen enriched combustion atmospheres. (October 2018) - Schluckner, C.; Gaber, C.; Demuth, M.; Forstinger, S.; Prieler, R.; Hochenauer, C.
Highlights: Flexible, experimentally validated scale formation model for two different steels. Scale formation kinetics for air-fuel, oxygen enriched and oxy-fuel combustion. Prediction of local and temporal scale formation rates during steel reheating. Local oxidizing species at steel surface determine the scale formation kinetics. Oxy-fuel combustion decreased reheating time and lowered scale losses. Abstract: This work presents a geometry-flexible, spatially resolved scale formation model for a mild and a tempering steel in high temperature reheating furnaces. Corresponding oxidation kinetics in air-fuel, oxygen enriched and oxy-fuel combustion atmospheres were developed to predict scale layer formation rates with high resolution in time and space. The results demonstrate the influence of different combustion atmospheres on the scale formation behaviour and highlight the local effects of oxidizing species. Finally, it was shown that oxygen enhanced and oxy-fuel combustion can be effectively used in reheating furnaces to minimize material losses, increase both productivity and efficiency and simultaneously reduce costs.